Peningkatan Kemampuan Pemecahan Masalah Geometri melalui Pembelajaran Kooperatif Berbasis Teori Van Hiele - Fona Fitry Burais; Husna Husna (Jurnal Peluang, 2018)
Geometry is a branch of mathematics that is taught with the aim that students can understand the properties and relationships between elements of geometry and can be a good problem solver. There are still many students who have difficulty learning geometry. One of the causes of students' difficulty in understanding geometry is that the learning strategies used are not in accordance with the material being taught. In addition, in geometry learning so far has not been adjusted to the level of development of students' thinking. Therefore an appropriate strategy is needed which is arranged based on the level of development of students' thinking in geometry. Van Hiele's theory-based learning is learning that is adapted to students' thinking stages, so this learning is appropriate if applied in geometry learning. The purpose of this study was to determine the improvement of geometry problem solving abilities between students taught by cooperative learning based on Van Hiele theory with conventional learning reviewed by students and based on student level. This study uses an experimental method with a pretest-posttest control group design design. The instrument used is a geometry problem solving test. The population in this study were students of class XII SMA Negeri 1 Sakti, Pidie Regency, Aceh Province, and the randomly selected sample consisted of two classes into the experimental class and the control class. The data analyzed is data N-gain problem solving ability. From the results of the data analysis, the improvement of students 'geometry problem solving abilities that obtain Van Hiele based learning is better than students who obtain conventional learning in terms of overall students and based on students' level of ability. Thus, in geometry learning it is recommended to apply learning based on Van Hiele theory so that students' geometry problem solving skills can be improved.